2021
DOI: 10.1186/s12864-021-07697-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the WRKY transcription factor family in flax (Linum usitatissimum L.)

Abstract: Background Members of the WRKY protein family, one of the largest transcription factor families in plants, are involved in plant growth and development, signal transduction, senescence, and stress resistance. However, little information is available about WRKY transcription factors in flax (Linum usitatissimum L.). Results In this study, comprehensive genome-wide characterization of the flax WRKY gene family was conducted that led to prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 85 publications
2
32
0
Order By: Relevance
“…Among them, ClWRKY20 , 21 , and 55 possessed a unique pattern “WNSIVV” which was conserved in these three members. Clustering of one domain WRKY of factors in group I is consistent with the study of the WRKY TF family in Linum usitatissimum ( Yuan et al, 2021 ). The same results are reported in Cicer arietinum ( Kumar et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Among them, ClWRKY20 , 21 , and 55 possessed a unique pattern “WNSIVV” which was conserved in these three members. Clustering of one domain WRKY of factors in group I is consistent with the study of the WRKY TF family in Linum usitatissimum ( Yuan et al, 2021 ). The same results are reported in Cicer arietinum ( Kumar et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Compared with some higher angiosperms, the LchiWRKY family has a smaller number. For example, there are 125 ZmWRKY genes in the maize ( Zea mays ) genome [ 43 ], 108 HbWRKY genes in the Rubber Tree ( Hevea brasiliensis ) genome [ 44 ], 102 LuWRKY genes in Flax ( Linum usitatissimum L.) genome [ 45 ], 86 HvWRKY genes in Barley ( Hordeum vulgare L.) genome [ 46 ], and 64 IiWRKY genes were identified in the whole genome of Isatis indigotica [ 47 ]. A total of 61 CsWRKY genes in the Cucumber ( Cucumis sativus L.) genome [ 4 ], 57 CmWRKY genes were identified in the melon ( Cucumis Melo L.) genome [ 48 ], and 54 AcWRKYs in Pineapple ( Ananas comosus (L.) Merr.)…”
Section: Discussionmentioning
confidence: 99%
“…With the development of molecular techniques, members of this gene family have been discovered in an increasing number of varied species. 74 WRKYs have been identified in Arabidopsis, 109 in rice [ 32 , 33 ], 104 in poplar [ 34 ], 102 in flax [ 35 ], 45 in Eucommia ulmoides [ 36 ], 57 in melon [ 37 ], 86 in barley [ 38 ], and 64 in Isatis indigotica [ 39 ]. Previous study also revealed 127 WRKY members in apple [ 25 ].…”
Section: Discussionmentioning
confidence: 99%